Adolescent Sexual Behavior in Cartintes Atambua Health Vocational School Belu District - Asa, Ansgaria Febriantika; Manurung, Imelda F. E; Riwu, Yuliana Radja; Purnawan, Sigit (Timorese Journal of Public Health, 2020)
Adolescent reproductive health can have a good impact and prevent the occurrence of deviations in sexual behavior among adolescents. Report from the Integrated Service Center for the Empowerment of Women and Children (P2TP2A) in Belu Regency in 2019, there were 102 cases of unwanted pregnancy and more cases of unwanted pregnancy occurred in young girls aged 15-19 years.(P2TP2A, 2019). The purpose of this study was to describe the factors that influence the sexual behavior of adolescents in the Cartintes Atambua Health Vocational School. This type of research is descriptive quantitative. The population in this study were 115 students of class XI and XII at SMK Kesehatan Cartintes Atambua and the sampling technique used was total sampling with a total of 115 people. The results of the analysis showed that there were 79 people (68.7%) who had good knowledge about reproductive health and 36 people (31.3%) had less knowledge. Permissive attitude towards sexual behavior as much78 people (67.8%) and non-permissive attitudes as many as 37 people (32.2%). The role of good peers as many as 100 people (87.0%) and the role of bad peers as much 15people (13.0%). There were 70 people (60.9%) who were not exposed to pornography media and 45 people (39.1%) were exposed to pornographic media. Adolescent sexual behavior among students of the Atambua Cartintes Health Vocational School as many as 113 people (98.3%) had done it and 2 people (1.7%) had never done sexual behavior. Suggestions for schools can provide materials related to Adolescent Reproductive Health (KRR), hold a Youth Information and Counseling Center (PIK-R) program in schools, and participate in supporting government programs related to adolescent problems